The Economic Impact of Renewable Energy Development in Indonesia - Fathul Nugroho; Noor Syaifuddin (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2017)
Renewable energy is believed to play a greater role in addressing climate change, economic development, and energy sustainability. Energy efficiency and renewable energy are similar with two sides of the same coin, that is, cannot be split. Currently, most of the developed countries are implementing energy efficiency while promoting renewable energy sources and technologies at the same time. It is well-known that renewable energy is one of the solutions for the sustainability of global energy system. Efforts to improve the share of renewable energy in transportation, industrial, and power generation sectors have been implemented in some countries. More countries in the world adopt renewable energy as alternative sources of energy in order to improve countryâ€™s energy efficiency. Indeed, however, the studies that deeply analyze the linkage between renewable energy and energy efficiency, as well as its economic impact, are still limited. Thus, this study attempts to find this linkage.Â Keywords: economic impact; renewable energy; GDPÂ